Capillary‐Venous Malformation in the Upper Limb. Issue 2 (5th January 2015) - Uihlein, Lily Changchien; Liang, Marilyn G.; Fishman, Steven J.; Alomari, Ahmad I.; Mulliken, John B.
Abstract: We present a group of patients with regional capillary malformations of the upper limbs and few additional findings other than prominent veins. We believe that this entity is the upper extremity equivalent of capillary‐venous malformation of the lower limb and, likewise, belongs at the minor end of the spectrum of vascular disorders with overgrowth.